Sediminibacillus dalangtanensis sp. nov., a moderate halophile isolated from hypersaline sediments of the Qaidam Basin in Northwest China. Issue 8 (24th August 2022) - Huang, Ting; Lai, Qiliang; Xiao, Long; Gong, Linfeng; Shao, Zongze; Wang, Hongmei; Xu, Yi; Amils, Ricardo; Escudero, Cristina; Martinez, José M.
Abstract : A Gram-stain-positive, moderately halophilic, aerobic, endospore-forming, rod-shaped bacterium, designated strain DP4-553-S T, was isolated from hypersaline sediment collected from the Dalangtan Playa in the Qaidam Basin, Northwest PR China. Growth occurred within 0–21.6% (w/v) NaCl (optimum 7.2%) at pH 5.5–9.0 (optimum pH 7.0) and at 4–45 °C (optimum 37 °C). Phylogeny based on 16S rRNA gene sequences indicated that strain DP4-553-S T belonged to the genus Sediminibacillus, with high 16S rRNA gene sequence similarity to Sediminibacillus halophilus EN8d T (99.5 %), Sediminibacillus terrae JSM 102062 T (99.4 %), Virgibacillus senegalensis SK-1 T (99.3 %) and Sediminibacillus albus NHBX5 T (98.3 %). The G+C content of the chromosomal DNA was 43.6 mol %. The average amino acid identity, average nucleotide identity and digital DNA–DNA hybridization values between strain DP4-553-S T and the four close type strains were 71.2–93.3, 74.0–90.5 and 20.0–41.4 %, respectively. The whole genomic analysis showed that strain DP4-553-S T constituted a different taxon separated from the recognized Sediminibacillus species. The major cellular fatty acids were anteiso-C15 : 0, anteiso-C17 : 0, iso-C16 : 0, C16 : 0 and iso-C15 : 0 . The type strain contained cell-wall peptidoglycan based on diaminopimelic acid and possessed menaquinone-7 as the major respiratory isoprenoid quinone. The polar lipid pattern consisted of diphosphatidylglycerol, phosphatidylglycerol, four unidentified glycolipids, phosphatidylcholine, aminophospholipid, aminolipid and seven unidentified phospholipids. The combined data from phenotypic and genotypic studies demonstrated that strain DP4-553-S T represents a novel species of the genus Sediminibacillus, for which the name Sediminibacillus dalangtanensis sp. nov. is proposed, the type strain is DP4-553-S T (=MCCC 1K03838 T = KCTC 43250 T ).